PENERAPAN COST VOLUME PROFIT MAIN PRODUCT DAN BYPRODUCT SEBAGAI ALAT BANTU PERENCANAAN LABA PADA PETERNAKAN AYAM SLOROK FARM - BONITA Y, DELVIYANA (Jurnal Akuntansi AKUNESA, 2018)
The rapid development of the business world has resulted in increasingly competitive competition among companies. In achieving optimal profit, the company needs a mature profit plan, accurate information on the relationship between cost, sales volume and profit. One of the profit planning tools that a company can use is cost volume profit. Cost volume profit can be used to determine the volume or sales revenue needed to achieve a specific BEP or profit target. Cost volume profit calcilation can be used contribution margin analyze, Break Even Point analyze, margin of safety analyze, degree of operating leverage, and profit planning. The purpose of this research is to know profit planning with cost-volume-profit implementation. This research was conducted at Chicken Farm of Slorok Farm Blitar. The result of this research is the Slorok Farm profit planning analysis with cost-volume-profit implementation. Keywords : Cost volume profit, Profit Planning, Chicken Farm